Investment Decisions Of Investors Based On Generation Groups - Mochammad Rizaldy Insan Baihaqqy; Sugiyanto (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2020)
This study aims to describe the effect of financial literacy in each generation group (Gen Z, Gen Y, Gen X, and Baby Boomers) in investment decision making. The method used in this research is quantitative descriptive. Respondents in this study were 137 investors who were members of the Indonesia Stock Exchange. Data collection was conducted in January 2020-February 2020. The results showed that the differences in financial literacy of each generation group had a significant influence on investment decisions. financial literacy and Investment experience is needed in the capital market in making investment decisions.